Synergy of artificial intelligence and blockchain in optimizing financial transactions and real-time auditing - Tabakova, Nataliia (Актуальні питання економічних наук, 2025)
Traditional centralised financial and auditing mechanisms are increasingly proving ineffective in addressing challenges such as fraud risks, data manipulation, and delays in transaction verification. Against this backdrop, the synergy of artificial intelligence (AI) and blockchain has become a key driver of innovation, ushering in a paradigm shift toward intelligent and decentralised financial ecosystems. The purpose of this study is to analyse how the integration of artificial intelligence algorithms and blockchain infrastructure can enhance the efficiency, transparency, and accountability of financial operations and auditing practices in real-time. Methods: analysis of scientific literature – to study the current state of research on the problem; generalisation and systematisation – to present the research results. The study's results demonstrate that the convergence of AI and blockchain technologies enables a transition from traditional post-event auditing and transaction verification to continuous, predictive, and self-regulating processes. AI contributes through machine learning, neural networks, and predictive analytics, supporting real-time anomaly detection, liquidity and risk forecasting, and autonomous transaction management. Blockchain complements these functions by ensuring data immutability, traceability, and decentralised validation, eliminating the need for intermediaries and guaranteeing the integrity of recorded information. The integration of AI-based analytics with blockchain-based smart contracts enables the automation of financial operations, where transactions are executed and verified simultaneously according to predefined algorithms. In the field of auditing, this integration supports continuous monitoring, rapid detection of irregularities, and complete transparency of operations, significantly increasing trust and compliance with regulatory standards. The conclusions emphasise that the integration of AI and blockchain not only improves the efficiency of financial systems but also transforms the very nature of financial management. It provides a technological foundation for real-time auditing, adaptive risk management, and autonomous financial decision-making. At the same time, implementing such systems requires addressing legal, ethical, and cybersecurity challenges to ensure a balanced integration of blockchain and AI into the global financial system.